Effect of Mixed Feed and Roughage for Fattening Cattle - PHIPHAKHAVONG, Sompaseuth; INTHAPANYA , Sangkhom; MANIVANH , Nouphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The objective of this study was to evaluate the effects of feed intake, growth performance and economic income of fattening cattle by using mixed feed at 25; 50 and 75% (the mixed feed included concentrate feed, cassava roots chips; brewer’s gains, urea, and vitamin) and the roughage as straw at 75; 50 and 25%. This experiment was arranged in a Randomized Completely Design (RCD) with 3 treatments and 4 replicates. Four male of high breed cattle (yellow cattle + Brahman cattle) per treatment with initial weight of 374.5kg were used. The treatments included (1) M25:R75= mixed feed 25% + roughage 75%; (2) M50:R50= mixed feed 50% + roughage 50%; and (3) M75:R25= mixed feed 75% + roughage 25%. The animals were offered ad-libitum into an individual cage. Feeds offered were weighed before giving them to the cattle. Feed refusals were collected each morning prior to offering fresh feed and weighed to measure the feed intake. The live weights of the cattle were taken at the beginning, every 30days and at the end of the experiment, using an electronic balance. The results were showed that the total feed intake was significant value (Pro<0.05) and the intake was increased by proportion of mixed feed and roughage (25%, 50%, and 75%), but there was higher for M75:R25 at 12.5% when compared with M50:R50 and M25:R75. The live weight change of cattle was increased after 30days of the trial periods. There was significant of growth rate (Pro<0.05) with higher treatment for M75:R25 when compared with M50:R50 and M25:R75, and was improved of growth rate for M25:R75 by 53.3% compared with both of treatments, respectively, and when increased the level of MF in the diets of 25%, 50% and 75% were increased profited.